(untitled) (Journal of Asian Development Studies, 2024)
The role of women is critical to bothaddressing the refugee crisis and promoting a planetary humanist perspective.By recognizing and valuing the contributions of women, we can work towards more equitable and sustainable solutions to global challenges.The paperattempts to explore the role of womenas‘volunteers’who play a crucial role in supporting and assisting the refugees in NadiaHashmi’snovel“when the moon is low”(2015).A lot of research hasbeen carried outon women refugees in terms of trials and tribulations that they face in their migration journeyincludinghow their experiences as refugees are different from those of malestakinginto account factors such as race, ethnicity, religion, class, and sexuality, but nosignificant work hasbeen doneon the non-refugee women who volunteer themselves, both formally and informally, to support and assist the refugees on ground level. Such a concept presents a positive step towards a planetary humanist approach.Thus, the study proposesthat it is paramount to consider the role of non-refugee women as volunteers in moving towards an all-inclusive planetary approach.To accomplish this, this paper aims to build a synapse between the notions of planetary humanism, refugee crisis, and volunteerismaspresented by numerous theorists on the relevant areassuchas Gilroy(2002), Phipps(2019), Lahusen, and Grasso(2018). Moreover, most of the work on volunteerism comprises field work based on quantitative analysis. This studyhowever, appliesthis idea to the refugee narrative